MATHEMATICAL ANALYSIS OF RAYLEIGH BEAM WITH DAMPING COEFFICIENT SUBJECTED TO MOVING LOAD - Usman, Mustaph; Adefala, T. A. (FUDMA Journal of Sciences, 2020)
In this paper, the mathematical analysis of Rayleigh beam with damping coefficient subjected to moving load is investigated. The governing partial differential equation of order four was reduced to an ordinary differential equation using series solution. Numerical result was presented and it is found that the dynamic response of the beam increases as the length of the mass increases, the same result is also found for the length of the beam and the mass of the load but the dynamic response of the beam decreases as the length of the load. It also reduces as the speed at which the load moves increases. Also, the dynamic response of the beam is not affected by the damping coefficient.
Keywords: Dynamic Response, Damping coefficient, Rayleigh Beam, Series Solution, Moving Load